Genetic background of primary and familial HLH in Qatar: registry data and population study - Elgaali, Elkhansa; Mezzavilla, Massimo; Ahmed, Ikhlak; Elanbari, Mohammed; Ali, Aesha; Abdelaziz, Ghada; Fakhro, Khalid A.; Saleh, Ayman; Ben-Omran, Tawfeg; Almulla, Naima; Cugno, Chiara (Frontiers in Pediatrics, 2024)
Familial Hemophagocytic Lymphohistiocytosis (FHLH) is an inherited life-threatening disease. Five types are identified with the addition of congenital immunodeficiency syndromes in which HLH is a typical manifestation. The literature on this disease is very scarce in the Middle East, with only a few scattered reports.We report detailed demographic, clinical, and genomic data from 28 patients diagnosed with primary and FHLH and Griscelli syndrome type 2 over the last decade in Qatar. Evaluation of allele frequencies of deleterious variants from 12 primary and FHLH causative genes was performed on the Qatar Genome Programme (QGP) cohort of 14,669 Qatari individuals.The genetic diagnosis was obtained in 15 patients and 4 novel mutations in PRF1, UNC13D, LYST and RAB27A genes were identified. We identified 22,945 low/high/moderate/modifier impact variants significantly enriched in the QGP in those 12 genes. The variants rs1271079313 in PRF1 and rs753966933 in RAB27A found in our patients' cohort were significantly more prevalent in QGP compared to the gnomAD database, with a high carrier frequency in the Qatari population.We established the first primary and FHLH Registry in the Gulf Region and identified novel possibly pathogenic variants present at higher frequency in the Qatari population, which could be used for screening purposes. Raising awareness about primary and FHLH and implementing screening activities in the Qatari highly inbred population could stem into more comprehensive pre-marital and prenatal evaluations and faster diagnosis.